Factors Affecting the Use of Evidence in Public Sector Programmes in South Africa: A Systematic Review of Outcome 8 programmes - Matlala, Lesedi Senamele (Conference on Digital Government Research, 2025)
The effective use of evidence is crucial for improving public sector programmes' design, implementation, and outcomes, particularly in addressing the complex challenges developing countries like South Africa face. Outcome 8 of the National Development Plan (NDP), which aims to transform human settlements and improve the quality of life for South African citizens, has been the subject of multiple evaluations since its introduction in 2010. Despite the availability of extensive evaluation data, integrating findings into policy and practice has often been inconsistent, with recurring issues identified across various evaluation cycles. This study systematically reviews the factors affecting the use of evidence generated from these evaluations in Outcome 8 programmes, specifically focusing on evaluations conducted from 2010 to the present. The review synthesizes government evaluations, policy reports, and academic literature to identify key barriers and facilitators in using evidence for policy-making and programme implementation. The findings reveal several barriers to evidence use, including political interference, which often influences the prioritization and implementation of evidence-based policies; limited capacity within government departments, hindering the interpretation and application of evaluation findings; and challenges in data consistency across national, provincial, and local government levels. Additionally, the review identifies that public sector programmes often rely predominantly on quantitative metrics, which may overlook the value of qualitative insights that could offer more context and a deeper understanding of policy impacts and outcomes. On the other hand, facilitators of evidence use, such as establishing strong institutional frameworks, forming evidence networks to promote knowledge exchange, and enhancing collaboration between evaluators and policymakers, were also highlighted. These facilitators help create an environment where evidence is more likely to inform policy decisions, leading to more effective governance and better programme outcomes. The review concludes by recommending strategies to address these barriers and improve the integration of evidence into policy-making and programme implementation. Key recommendations include strengthening the capacity of public sector officials to interpret and apply evaluation findings, promoting collaboration between evaluators and policymakers, and institutionalizing the use of evidence across government departments. Overcoming these challenges is crucial for improving the effectiveness of Outcome 8 programmes, advancing the broader goals of human settlement transformation in South Africa, and enhancing the impact of public policies.